Strategies for Managing Preoperative Anxiety in Children: A Comprehensive Approach - Riswandi, Riswandi; Santoso, Kohar Hari; Andriyanto, Lucky (Nusantara Medical Science Journal, 2025)
Introduction: Preoperative anxiety is prevalent among pediatric patients and may adversely affect anesthetic induction, postoperative recovery, and long-term psychological outcomes. It arises from developmental vulnerability, lack of understanding, and exposure to unfamiliar environments. Method: This narrative review synthesizes evidence from studies retrieved via PubMed, ScienceDirect, and EBSCO, using keywords related to preoperative anxiety, pediatric patients, and management strategies. The review explores both risk factors and intervention modalities. Results: The database search using predefined keywords yielded a total of 193 articles. After screening and eligibility assessment, 22 articles met the inclusion criteria and were included in this literature review. Conclusions: A comprehensive, individualized approach combining both pharmacological and non-pharmacological strategies is essential to effectively manage preoperative anxiety in children. Early identification of risk factors and tailored interventions can significantly enhance perioperative experiences and outcomes.